Interdictions & Benedictions–AIDS Prevention Discourses in Vancouver Canada - John Egan (Adult Education Research Conference, 2000)
AIDS education has brought discourses regarding (homo)sexuality into the mainstream. This study of prevention-related artifacts from Vancouver analyzes key discursive aspects of local AIDS prevention programs.